Investigation of genome instability in patients with non-alcoholic steatohepatitis - Karaman, Hatice (World journal of gastroenterology : WJG, 2013)
To evaluate the occurrence of micronucleus (MN), nucleoplasmic bridges (NPBs) and nuclear buds (NBUDs) in the mitogen-stimulated lymphocytes of patients with non-alcoholic steatohepatitis (NASH). The study was performed in 25 (9 females, 16 males) patients newly diagnosed with NASH, and 25 healthy subjects of similar ages and genders were used as a control group. None of the controls was known to be receiving any drugs for medical or other reasons or using alcohol. Hepatosteatosis was further excluded by abdominal ultrasound imaging in the control group. The numbers of MN, NPBs and NBUDs scored in binucleated (BN) cells were obtained from the mitogen-stimulated lymphocytes of patients and control subjects. Statistical comparisons of the numbers of BN cells with MN, NPBs and NBUDs and ages between the patients with NASH and control subjects were performed. The mean ages of the patients and the control group were 41.92 ± 13.33 and 41.80 ± 13.09 years (P > 0.05), respectively. The values of the mean body mass index (BMI), HOMA-IR, hemoglobin, creatinin, aspartate aminotransferase, alanine aminotransferase, triglyceride, high density lipoprotein, and low density lipoprotein were 31.19 ± 4.62 kg/m(2) vs 25.07 ± 4.14 kg/m(2), 6.71 ± 4.68 vs 1.40 ± 0.53, 14.73 ± 1.49 g/dL vs 14.64 ± 1.30 g/dL, 0.74 ± 0.15 mg/dL vs 0.80 ± 0.13 mg/dL, 56.08 ± 29.11 U/L vs 16.88 ± 3.33 U/L, 92.2 ± 41.43 U/L vs 15.88 ± 5.88 U/L, 219.21 ± 141.68 mg/dL vs 102.56 ± 57.98 mg/dL, 16.37 ± 9.65 mg/dL vs 48.72 ± 15.31 mg/dL, and 136.75 ± 30.14 mg/dL vs 114.63 ± 34.13 mg/dL in the patients and control groups, respectively. The total numbers and frequencies of BN cells with MN, NPBs and NBUDs, which were scored using the CBMN cytome assay on PHA-stimulated lymphocytes, were evaluated in the patients with NASH and control group. We found significantly higher numbers of MN, NPBs and NBUDs in the BN cells of patients with NASH than in those of the control subjects (21.60 ± 9.32 vs 6.88 ± 3.91; 29.28 ± 13.31 vs 7.84 ± 3.96; 15.60 ± 5.55 vs 4.20 ± 1.63, respectively, P < 0.0001). The increased numbers of MN, NPBs and NBUDs observed in the lymphocytes obtained from patients with NASH may reflect genomic instability.